Autoimmunity associates with severity of illness in elderly patients with drug-induced liver injury - Xiong, Yu-Ting; Wang, Jian-Fei; Niu, Xiao-Xia; Fu, Yi-Ming; Wang, Ke-Xin; Wang, Chun-Yan; Li, Qian-Qian; Wang, Jian-Jun; Zhao, Jun; Ji, Dong (Frontiers in Pharmacology, 2023)
Drug-induced liver injury (DILI) is a potentially serious adverse drug reaction. Due to the lack of definite etiology, specific clinical manifestations, and diagnostic methods, its prediction and diagnosis are challenging. Elderly individuals are deemed to be at high risk for DILI due to abnormal pharmacokinetics, aging tissue repair function, comorbidities, and taking multiple drugs. This study aimed to identify the clinical characteristics and explore the risk factors associated with the severity of illness in elderly patients with DILI. In the present study, the clinical characteristics at the time of liver biopsy of consecutive patients with biopsy-proven DILI who presented at our hospital from June 2005 to September 2022 were evaluated. Hepatic inflammation and fibrosis were assessed according to the Scheuer scoring system. The presence of autoimmunity was considered if IgG level >1.1×ULN (1826 mg/dL), or high titer (>1:80) of ANA, or SMA. In total, 441 patients were enrolled, and the median age was 63.3 years (IQR, 61.0-66.0); 122 (27.7%), 195 (44.2%), or 124 (28.1%) were classified as having minor, moderate, or severe hepatic inflammation, respectively; and 188 (42.6%), 210 (47.6%) or 43 (9.8%) patients presented minor, significant fibrosis or cirrhosis, respectively. Female sex (73.5%) and the cholestatic pattern (47.6%) were dominant in elderly DILI patients. Autoimmunity existed in 201 patients (45.6%). Comorbidities were not directly associated with the severity of DILI. PLT (OR: 0.994, 95% CI: 0.991-0.997; p < 0.001), AST (OR: 1.001, 95% CI: 1.000-1.003, p = 0.012), TBIL (OR: 1.006, 95% CI: 1.003-1.010, p < 0.001), and autoimmunity (OR: 1.831, 95% CI: 1.258-2.672, p = 0.002) were associated with the degree of hepatic inflammation. Meanwhile, PLT (OR: 0.990, 95% CI: 0.986-0.993, p < 0.001), TBIL (OR: 1.004, 95% CI: 1.000-1.007, p = 0.028), age (OR: 1.123, 95% CI: 1.067-1.183, p < 0.001), and autoimmunity (OR: 1.760, 95% CI: 1.191-2.608, p = 0.005) were associated with the stage of hepatic fibrosis. This study revealed that the presence of autoimmunity represents a more serious illness state of DILI, deserving more intensive monitoring and progressive treatment.